Stakeholder perceptions of lethal means safety counseling: A qualitative systematic review - Khazanov, Gabriela Kattan; Keddem, Shimrit; Hoskins, Katelin; Myhre, Karoline; Sullivan, Sarah; Mitchell, Emily; Holliman, Brooke Dorsey; Landes, Sara J.; Simonetti, Joseph (Frontiers in Psychiatry, 2022)
Introduction: Lethal means safety counseling (LMSC) is an evidence-based suicide prevention intervention during which providers encourage patients to limit their access to lethal means (e.g., firearms, medications). Despite agreement about the importance of LMSC, it is underutilized in clinical practice. Methods: To better understand the individual and contextual factors that influence LMSC and its implementation, we conducted a systematic review of qualitative studies examining stakeholder perceptions of the intervention. PubMed and PsycInfo were searched up to February 2021 using terms related to: (1) LMSC, firearms, or medications; (2) suicide, safety, or injury; and (3) qualitative methodology. Two coders used thematic synthesis to analyze findings from eligible papers, including developing a codebook and coding using an inductive and iterative approach (reliability k>.70). Confidence in review findings were evaluated using the Confidence in the Evidence from Reviews of Qualitative Research (CERQual) Approach. Subthemes were assigned to domains in the Consolidated Framework for Implementation Research. Findings: Of the 19 papers identified, 18 discussed LMSC for firearms and 1 focused exclusively on LMSC for medications. The firearm-related studies explored perspectives of a variety of stakeholders (patients, providers, members of the firearms community, healthcare leaders, and family members) across multiple settings (emergency departments, pediatric and adult primary care, and outpatient mental health). Seven overarching themes emerged, including the: (1) importance of firearms to owners’ identities and perceptions of ownership as a value and right, which can lead to perceived cultural tensions in clinical settings; (2) importance of patients understanding the context and rationale for LMSC; (3) value of providers showing cultural competency when discussing firearms; (4) influence of safety and risk beliefs on firearm behaviors; (5) need to navigate logistical concerns when implementing LMSC; (6) value of individualizing LMSC; (7) potential for trusted family members and friends to be involved in implementing LMSC. Conclusions: This synthesis of the qualitative literature informs clinical, operational, and research endeavors aimed at increasing the reach and effectiveness of LMSC. Future research should address the perspectives of individuals underrepresented in the literature (e.g., those from racial/ethnic minority groups) and further examine stakeholders’ perceptions of LMSC for medication.